KAJIAN HUKUM TERHADAP FAKTOR PENYEBAB TERJADI TINDAK PIDANA PENELANTARAAN ISTRI OLEH SUAMI (Studi di Desa Meunasah Manyang kabupaten Aceh Besar) - Fitriani, Fitriani; Siahaan, Ade Yuliany (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
This study aims to find out the factors that cause the crime of abandonment of wives by husbands in the village of Meunasah Manyang, Kec. Krueng Barona Jaya, Kab. Aceh Besar and what efforts can be made in preventing the occurrence of abandonment carried out by husband to wife in the village of Meunasah Manyang, Kab, Aceh Besar.This Research is a Normative juridical method in addition to this research supported by empirical research through interviews. The results showed that the factors causing abandonment in Meunasah Manyang Village are First: economic factors, economic factors are the main factors that cause the crime of ejection, secondly: infidelity factors, third: intervention factors from third parties, fourth: husband factors gambling and fifth: namely factors working wives or wives have their own income, in Meunasah Manyang Village there are some cases of abandonment carried out by husbands not want to report things law enforment officials, prevention efforts carried out by the village head Meunasah Manyang by taking a persuasive approach by giving to victims.